Guerra y Paz en América Central - Llaguno Thomas, Esteban (2012)
In this intervention I refer to the process of permanent state of war in Central America, this way to raise the need of an open to dialog philosophy and performer opposite to the problematic social ones, depending on constructing a liberating project and of autonomy.